Pyogenic granuloma causing midline diastema: A rare case report - Anjan Jana; Santanu Mukhopadhyay; Abu Faijal Karim (Journal of Oral Research and Review)
This case report describes the presentation and management of a 12-year-old female patient with a tissue mass and spacing between her upper front teeth. Clinical examination revealed a reddish pink, lobulated tissue mass measuring approximately 1.5 cm × 2 cm, extending from the upper labial frenum to the incisive papilla and involving the interdental gingiva of the two central incisors. The mass was moderately firm, pedunculated, and prone to bleeding. The patient had poor oral hygiene, exacerbating the condition. Radiographic evaluation ruled out underlying bony lesions, leading to a provisional diagnosis of pyogenic granuloma with differential diagnoses of gingival fibroma or traumatic fibroma. The treatment plan involved excision of the gingival overgrowth and frenectomy. Following routine oral prophylaxis, the surgical procedure was performed, with the excised tissue sent for histopathological evaluation, confirming the diagnosis as pyogenic granuloma. Postoperative care was provided, and the patient was advised against active orthodontic treatment. Regular follow-up appointments were scheduled to monitor healing and spontaneous space closure. This case report underscores the significance of considering both the aberrant labial frenum and the gingival overgrowth in treatment planning and highlights the need for meticulous follow-up care.